2019
DOI: 10.14419/ijans.v8i2.29316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Program on Fatigue and Depression among Geriatric Patients Undergoing Hemodialysis

Abstract: Background: Fatigue is one of the foremost common complications faced the hemodialysis elderly patients. Fatigue not only impact the daily lives and activities of patients but it conjointly influences their quality of life, which can afterwards result in magnified depression, tiny social interactions and increase dependency on others.Aim: Determine the effect of exercise program on fatigue and depression among geriatric patients undergoing hemodialysis.Design: Randomized controlled trial (pretest post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Global Kidney Health Atlas (GKHA) indicated that the average number of new ESRD diagnoses was 144 individuals per million worldwide to general populations (International Society of Nephrology, 2019). In Egypt the estimated annual incidence of ESRD is around 74 per million (Abd Elhameed & Fadila, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Global Kidney Health Atlas (GKHA) indicated that the average number of new ESRD diagnoses was 144 individuals per million worldwide to general populations (International Society of Nephrology, 2019). In Egypt the estimated annual incidence of ESRD is around 74 per million (Abd Elhameed & Fadila, 2019).…”
Section: Introductionmentioning
confidence: 99%